Problems, Challenges and Prospects of Indonesian Muslim Community in Sydney for Promoting Tolerance - Muttaqin, Ahmad; Arifin, Achmad Zainal; Wajdi, Firdaus (Universitas Negeri Semarang, 2016)
This paper elucidates a map of Indonesian Muslim communities around Sydney in order to observe the possibility to promote a moderate and tolerance of Indonesian Islam worldwide. Indonesian Muslims who live in Australia are relatively small if we consider that we are the closer neighbor of Australia and have the biggest Muslim populations in the world. Most Indonesian Muslim communities in Sydney are in a form of kelompok pengajian (Islamic study group), which is commonly based on ethnicity, regionalism (province and regency), and religious affiliation with Indonesian Islamic groups. The main problems of Indonesian Muslim communities in Sydney are an ambiguous identity, laziness integration, and dream to home country. Most Indonesian Muslim diaspora in Sydney only consider Australia as the land for making money. Therefore, their inclusion to Australian community is just being âIndonesian Muslim in Australiaâ and it seems hard for them to be âAustralian Muslimâ, especially in the case of those who already changed to be Australian citizens. This kind of diaspora attitude differs from Muslims Diasporas from the Middle East and South Asia countries who are mostly ready to be fully Australian Muslim.Â Naturally, most Indonesian Muslim communities put their emphasis to develop their community based on social needs and try to avoid political idea of Islamism. In this case, the Indonesian government, through the Indonesian Consulate in Sydney, has great resources to promote moderate and tolerant views of Indonesian Islam to other Muslim communities, as well as to Western media. In optimizing resources of Indonesian Muslim communities in Sydney to envoy Indonesian cultures and policies, it is necessary for Indonesian government to have a person with integrated knowledge on Islamic Studies who are working officially under the Indonesian consulate in Sydney. Â It is based on the fact that most Indonesian Muslim communities needs a patron from the government to manage and soften some differences among them, especially related to problems of identities, as well as to link them with the wider Australian communities.